Coupling surface flow with high-performance subsurface reactive flow and transport code PFLOTRAN. (March 2021) - Wu, Runjian; Chen, Xingyuan; Hammond, Glenn; Bisht, Gautam; Song, Xuehang; Huang, Maoyi; Niu, Guo-Yue; Ferre, Ty
Abstract: Water exchange between the surface and subsurface is important for both water resource management and environmental protection. In this paper, we develop coupled surface and subsurface flow simulation capability in a parallel subsurface flow and reactive transport code PFLOTRAN. We sequentially couple the diffusion wave-based surface flow with the subsurface flow governed by the Richards equation in PFLOTRAN. These two flow domains are linked with a boundary condition switching method that ensures the continuity of pressure and flux at the surface-subsurface interface. We verify the coupled code against other existing hydrologic models and observation data using a number of numerical experiments. The coupled hydrological model exhibits good performance in strong parallel scaling tests. The new coupled surface and subsurface simulator significantly advance community simulation capability towards improving integrated hydrologic and biogeochemical understanding of complex systems such as watersheds and river corridors. Highlights: We developed coupled surface and subsurface flow simulation capability in PFLOTRAN. The surface and subsurface flow domains are linked with a boundary condition switching method. The newly coupled simulation capability are verified against other existing hydrologic models. The new capability demonstrates good parallel performance in strong scaling tests.